Turnover intention among employees in the restaurant industry: a lesson learned from Covid-19 pandemic - Ghazali, Hazrina; Mansor, Zuraina; Ishak, Maisarah; Anuar, Nurul Izzah (Human Resource Management Academic Research Society (HRMARS), 2023)
The COVID-19 pandemic has adversely impacted the restaurant industry and its employees. There is no questions that during COVID-19 it was very challenging times for both, employers and employees. During this time, many restaurants faced a huge loss of sales, resulting in many of them being cash strapped and, as a result, unable to fulfil their employee commitments. By no fault of theirs, employees are often faced with work insecurities. As their employers are pushed into a retrenchment exercise to save their company, many employees have had to accept a pay cut or have faced the risk of losing their jobs. This study aimed to examine potential factors that contribute towards the turnover intent among restaurant employees in restaurant industry during COVID-19 pandemic. Besides, this study also identified the most influential factors for turnover intent in restaurant industry. Furthermore, this study also to examine the relationship between demographic characteristics and turnover intent. The factors that used to conduct this study were job satisfaction, job engagement, and job insecurity. This study used quantitative approach through an online self-administered survey. Questionnaires were distributed through an online platform and there were only 125 valid questionnaires returned for further analysis. Data obtained were analysed by using Statistic Packages for Social Science (SPSS) latest version. Based on the analysis, job satisfaction (0.349) was the most influential factor of turnover intent and followed by job insecurities (0.294). Meanwhile, job engagement (0.066) factor did not significantly influence the turnover intent among the restaurant employees in this industry. Findings of this study intended to help managers or the strategic management division of the organisation identify factors that contribute to employee turnover intentions during pandemics and develop tactical solutions to deal with them in the future, should an unanticipated pandemic occur again. Although it is difficult to predict the future, it is crucial that we utilise what we learn from what had happened to direct our future.